2017
DOI: 10.1093/heapol/czx041
|View full text |Cite
|
Sign up to set email alerts
|

Are scientific research outputs aligned with national policy makers’ priorities? A case study of tuberculosis in Cambodia

Abstract: With funding for tuberculosis (TB) research decreasing, and the high global disease burden persisting, there are calls for increased investment in TB research. However, justification of such investments is questionable, when translation of research outputs into policy and health care improvements remains a challenge for TB and other diseases. Using TB in Cambodia as a case study, we investigate how evidence needs of national policy makers are addressed by topics covered in research publications. We first condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…To do this, we need to understand the range of impacts of COVID-19 on TB and HIV services, and identify feasible strategies for mitigation. Information from frontline health professionals and researchers is invaluable and often insufficiently incorporated into policy planning or in the formation of research questions [10,11]. In light of this, our study rapidly synthesised information from professionals working in affected countries, in order to identify both how COVID-19 is impacting TB and HIV services in LMIC and their recommendations for minimising disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we need to understand the range of impacts of COVID-19 on TB and HIV services, and identify feasible strategies for mitigation. Information from frontline health professionals and researchers is invaluable and often insufficiently incorporated into policy planning or in the formation of research questions [10,11]. In light of this, our study rapidly synthesised information from professionals working in affected countries, in order to identify both how COVID-19 is impacting TB and HIV services in LMIC and their recommendations for minimising disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Cambodia’s TB strategic plan for 2021 through 2030 includes increasingly early identification of TB cases, providing sustained and equitable access to high quality TB services, and preventing TB transmission through awareness and behavioral communication strategies [ 25 , 26 ]. The national TB program mainly concerns key and vulnerable populations including people living with HIV, elderly people (aged 55 and older), children, and people with diabetes [ 27 , 28 ]. A systematic assessment of TB trends with the inclusion of these key populations may further assist in monitoring Cambodia’s national TB goals and priorities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, engagement of policy-makers and users of research in shaping and conducting the studies that are funded is closely related to action of research findings, as demonstrated in a study by Kok et al [23]. In line with this concern, a recent analysis found that TB research conducted in Cambodia aligns poorly with domestic policy-makers’ priorities [24], and our findings may reflect a wider issue related to global agendas for health research being poorly aligned with local needs [25]. Although the recommendation to increase the number of stakeholders involved in prioritisation processes appears straightforward, we acknowledge the challenges in finding a balance between productivity (agreeing on a relatively small list of research priorities in the time available) and inclusion (including all voices and perspectives).…”
Section: Discussionmentioning
confidence: 99%